How to Think about Criminal Justice Reform: Conceptual and Practical Considerations - Kubrin, Charis Elizabeth (American journal of criminal justice, 2022)
How can we improve the effectiveness of criminal justice reform efforts? Effective reform hinges on shared understandings of what the problem is and shared visions of what success looks like. But consensus is hard to come by, and there has long been a distinction between "policy talk" or how problems are defined and solutions are promoted, and "policy action" or the design and adoption of certain policies. In this essay, we seek to promote productive thinking and talking about, as well as designing of, effective and sustainable criminal justice reforms. To this end, we offer reflections on underlying conceptual and practical considerations relevant for both criminal justice policy talk and action.